An experimental and numerical investigation on low velocity impact response of GLAREs. (1st September 2021) - Azhdari, Soroush; Fakhreddini-Najafabadi, Sajjad; Taheri-Behrooz, Fathollah
Abstract: Glass fiber aluminum laminates (GLAREs) are a type of fiber metal laminates (FMLs) that are widely used in the aviation industry. The present article aimed to carry out the numerical and experimental study of the damage mechanism initiation and development in the FMLs subject to low velocity impact. In the experimental part, the drop weight impact test was conducted at four energy levels of 8, 11.5, 15, and 18.5 J on the GLARE laminates. The first crack in the aluminum layer was observed at 18.5 J in the lower aluminum layer. In the numerical simulation, the user-material subroutine VUMAT, including the three-dimensional Hashin damage initiation criterion and the modified progressive damage evolution model, was coded and implemented in the ABAQUS/Explicit finite element package to predict damage initiation and development. The numerical simulations were validated by the experimental results in terms of force–time, force–displacement, and absorbed energy-time curves. The optical microscopy (OM) and scanning electron microscopy (SEM) images of the specimen cross-section were produced to detect the FML damage pattern. The numerical simulation and experimental results showed to be in good agreement.